Towards a clarification of the history of the Slovene river name Soča - Repanšek, Luka (Linguistica (Ljubljana), 2015)
The etymology of the Slovene hydronym Soča (Standard Friulan Lusinç, Italian Isonzo) was satisfactorily elucidated more than half a century ago. The overall idea that the river name goes back to a derivative of a Proto-Indo-European verbal root (...) is undoubtedly correct (the exact meaning of the root in question has, however, not been sufficiently corroborated) but the details remain hopelessly obscure. Given the contemporary reflexes of the underlying name (viz. Friulan Lusinç ~ dial. Lisuns etc.) and the sometimes conflicting or not at all easily reconcilable historical attestations (spanning nearly a millenium), no consensus can in fact be reached about the exact formal means involved in the derivation of the original deverbative formation - a fact which results from the overall inconvenience of sheer wealth of combinatorial possibilities that go hand in hand with the general ambiguity of the phonology more or less directly reflected by the later reflexes of the name. The present contribution is an attempt at unifying all the reliable data at our disposal into a coherent picture that would bring a satisfactory answer as to the exact phonological and morphological make-up of the pre-historic source (alongside with the reconstructed meaning) and its subsequent history as it passed through the various linguistic strata.
Keywords: etimologija; étymologie; etymology; hydronymes; Slovene; slovenščina; Soča (reka); toponymes; vodna imena; zemljepisna imena